A

6/2(1+2)=?

10 Answers
MDAS?...share your answer
E

We can use the mnemonic PEMDAS - Parenthesis (or bracket) - Exponent - Multiplication - Division - Addition - Subtraction with the note that multiplication / division have the same order and addition / subtraction have the same order.

The way that the equation was written; it can be interpreted in 2 ways:

A. 6
---------
2 (1+2) OR

B. 6
-------- X (1+2)
2

when we used the slash sign it is not clear if the numerals(1+2) inside the parenthesis is part of the divisor or if it is part of the dividend:

6 = dividend
------
2 = divisor

If (1+2) is part of the divisor then we can use equation A where in the answer will be

6 6 6
--------- = ---------- = ------ = 1
2 (1+2) 2(3) 6

If (1+2) is part of the dividend then we can use equation B wherein the answer will be

6
-------- * (1+2) = 3 * (1+2) = 3*3 = 9
2

...
A

The full mnemonic is PEMDAS (Parenthesis, Exponent, Multiplication, Division, Addition and Subtraction).

First simplify parenthesis: 1 + 2 is 3, hence the number equation becomes 6/2(3)
Then, multiplication: 6 times 3 is 18, hence the equation becomes 18/2
Then division: 18 divided by 2 is 9, hence the result is 9.

In the above procedure, division of 6 by 2 can be done before multiplication, since multiplication and division have the same order, as do addition and subtraction.

...
I

I will use the formula of BODMAS to solve it.

B=Bracket
O=Or
D=Division
M=Multiplication
A=Addition
S=Subtraction

So, here it goes...

6/2(1+2)
=6/2(3)
=3(3)
=9

The answer is 9

...
G

Here we will use BODMAS rule to solve the problem. BODMAS stands for bracket ,off,division,multiply,add,substract. So here we will first simplify brackets so
6/2(1+2) = 6/2*3 = 3*3 = 9

...
T

We solve this question by BODMAS method we start solving first we solve bracket then division and then multiplication
6/2(1+2) =6/2(3)
=3*3
=9
so, answer is 9

...
E

Kindly ignore the misplaced number on the 8th paragraph; it should be written like this...thanks

6 6 6
--------- = ---------- = ------ = 1
2 (1+2) 2(3) 6

...
C

It uses PEMDAS ( Parenthesis, Exponent, Multiplication, Division, Addition, Subtraction)

X = 6/2 (1+2)
= 6/2(3)
= 6/6
X = 1

...
J

6 / 2 (1 + 2) = ?

6 / 2 = 3

1 + 2 = 3

3 (3) = 9
or 3 x 3 = 9

...
A

I saw this thing somewhere...

6/2(3)
then
2(3)
then
6/6
=1

...
B

Using bodmas we start with brackets [1+2]=3 then 6/2=3 so the equation becomes 3[3]=3*3=9

...